Adsorption of nickel(II) from aqueous solution onto activated carbon prepared from almond husk - Hasar, H (Elsevier Science Bv, 2003)
Activated carbon was prepared from almond husk by activating without (MAC-I) and with (MAC-II) H2SO4 at different temperatures. The ability of the activated carbon to remove nickel(II) ions from aqueous solutions by adsorption has been investigated under several conditions such as pH, carbonisation temperature of husk, initial concentration of metal ions, contact time, and adsorbent concentration. Optimal conditions were pH 5.0, the carbonisation temperature of 700degreesC, 50 min of contact time and adsorbent concentration of 5 g/l. The results indicate that the effective uptake of Ni(II) ions was obtained by activating the carbon, prepared from almond husk at 700degreesC, through the addition of H2SO4. The removal of Ni(II) were found to be 97.8% at initial concentration of 25 mg/l and the adsorbent concentration of 5 g/l. When the adsorbent concentration was increased up to 40 g/l, the adsorption density decreased from 4.89 to 0.616 mg/g for MAC-II. In the isotherm studies, the experimental adsorption data fitted reasonably well the Langmuir isotherm for both MAC-I and MAC-II. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: nickel(II) uptake; activated carbon; almond husk; adsorption isotherm